There Are at Most Finitely Many Singular Moduli That Are S-Units - Herrero-Miranda, S (Cambridge University Press, 2024)
We show that for every finite set of prime numbers S, there are at most finitely many singular moduli that are S-units. The key new ingredient is that for every prime number p, singular moduli are p-adically disperse. We prove analogous results for the Weber modular functions, the λ-invariants and the McKay–Thompson series associated with the elements of the monster group. Finally, we also obtain that a modular function that specializes to infinitely many algebraic units at quadratic imaginary numbers must be a weak modular unit. © 2024 The Author(s).